Distributed Autonomous Robotic Systems 3 1998
DOI: 10.1007/978-3-642-72198-4_28
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Modelling of a Bio-Inspired Collective Experiment with Real Robots

Abstract: Abstract. This paper describes the implementation and modelling of a biologically inspired collective behaviour. The experiments are concerned with the gathering and clustering of randomly distributed small cylinders. Each experiment has been repeated ten times in a simulated environment (parametric simulation) and carried out five times with a group of ten Khepera miniature mobile robots. The simulated and experimental results are compared, quantified and discussed showing the advantages and the weaknesses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Autonomy has been studied in bio-inspired [39] and decentralized peer-to-peer [40,41] approaches, which are particularly good at decomposing large or complex problems otherwise hard to tackle using standard centralized solutions. Autonomy also directly refers to intelligent and multi-agent systems [42] in general, where coordination and distributed problem planning/solving are tackled using distributed artificial intelligent techniques.…”
Section: Dynamics In Decentralized Settingsmentioning
confidence: 99%
“…Autonomy has been studied in bio-inspired [39] and decentralized peer-to-peer [40,41] approaches, which are particularly good at decomposing large or complex problems otherwise hard to tackle using standard centralized solutions. Autonomy also directly refers to intelligent and multi-agent systems [42] in general, where coordination and distributed problem planning/solving are tackled using distributed artificial intelligent techniques.…”
Section: Dynamics In Decentralized Settingsmentioning
confidence: 99%
“…The behavior of ant colonies has also inspired research in robotics, in particular for the design of distributed control algorithms for groups of robots [111]. An example of a task that has been used as a benchmark for ant algorithms applied to distributed robotics problems is cooperative box pushing [112].…”
Section: Algorithms Inspired By Cooperative Transportmentioning
confidence: 99%
“…Martinoli and Mondada [30] performed parametric simulations and real experiments for a clustering task using multiple robots. They found that the main difference is that the performance of a team of three real robots is less rapidly saturated than in simulation.…”
Section: Interferencementioning
confidence: 99%